2017
DOI: 10.1002/rcm.7838
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic half‐life and enrichment factor in two species of European freshwater fish larvae: an experimental approach

Abstract: Metabolic rates seemed lower for chub than for roach, especially when they were fed with Chironomidae. A Chironomidae-based diet would be more profitable to chub, and the high associated growth rate could increase the development of the fish larvae. The HL and TEF were in the range of those reported in the literature. These results will be helpful for field-based studies, because they can help to increase the accuracy of models. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(118 reference statements)
1
2
0
Order By: Relevance
“…Our results confirmed that isotopic carbon and nitrogen half‐lives of first‐feeding rainbow trout were clearly influenced by the quality of the protein (animal versus plant). The half‐lives we estimated ranged from 7–16 days, which were similar to those for other fish species of similar age (Latli et al., 2017; Weidel et al., 2011). Carbon and nitrogen isotopic incorporation rates were lower for fry fed CGM than for fry fed MixM.…”
Section: Discussionsupporting
confidence: 85%
“…Our results confirmed that isotopic carbon and nitrogen half‐lives of first‐feeding rainbow trout were clearly influenced by the quality of the protein (animal versus plant). The half‐lives we estimated ranged from 7–16 days, which were similar to those for other fish species of similar age (Latli et al., 2017; Weidel et al., 2011). Carbon and nitrogen isotopic incorporation rates were lower for fry fed CGM than for fry fed MixM.…”
Section: Discussionsupporting
confidence: 85%
“…The isotopic variations of potential food sources were characterised by the mean of the taxa family (± SD ) and the abundance of each taxon analysed (Supporting Information Appendix S1). The MixSIAR models were constructed using trophic enrichment factors determined previously by the authors during a controlled experiment targeted on YOY of the studied species (Latli, Sturaro, et al., ) and with the formula proposed by Caut, Angulo, and Courchamp () for adults. To reduce the number of potential food sources in the model, we pooled prey types if stable isotope values were not statistically different as proposed by Phillips et al.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the contributions of potential food sources for each species for each date of sampling with the R-software (R 3.6.2 version, R Development Core Team, 2016) using the package MixSIAR (Stock et al, 2018). The MixSIAR models were constructed using trophic enrichment factor (TEF) determined previously by Latli et al (2017) that concerned chub fish larvae (TEF = 2.1‰ ± 0.03 for δ 13 C and 2.3‰ ± 0.8 for δ 15 N). Standard error of the δ 13 C was finally increased until 0.5 ‰ giving a better accuracy of the models.…”
Section: Food Resources Fish Sampling and Isotope Measurementsmentioning
confidence: 99%